In situ electrochemical dilatometry study of capacity fading in nanoporous Ge-based Na-ion battery anodes. (15th April 2019) - Li, Manni; Wang, Zeyu; Fu, Jintao; Ma, Ke; Detsi, Eric
Abstract: It is found that crystalline nanoporous Ge can only partially store sodium, with amorphous Nax Ge as the sodiation product. Electrochemical dilatometry techniques were used to measure the corresponding (de)sodiation-induced strains. The capacity and strain amplitude were found to exhibit the same decay trend during long-term cycling, which is expected since the capacity fades because of the volume changes arising during cycling. However, viewed from a different perspective, the similarity between capacity fading and strain decay suggests that one way to mitigate this capacity fading might be by preventing the initial strain from decaying, instead of getting rid of this strain. Graphical abstract: Unlabelled Image